Answer:
<h3>
-2a³ + 9a² + 6ab² + 45a + 18b² </h3>
Step-by-step explanation:
(a + 3)×(−2a² + 15a + 6b²) =
= a×(−2a² + 15a + 6b²) + 3×(−2a² + 15a + 6b²) =
= -2a³ + <u>15a²</u> + 6ab² - <u>6a²</u> + 45a + 18b² =
= -2a³ + 9a² + 6ab² + 45a + 18b²
- Quadratic Formula:
, with a = x^2 coefficient, b = x coefficient, and c = constant
With our equation, plug in the values:
![x=\frac{4\pm \sqrt{(-4)^2-4*1*13}}{2*1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%5Cpm%20%5Csqrt%7B%28-4%29%5E2-4%2A1%2A13%7D%7D%7B2%2A1%7D)
Next, solve the exponent and multiplications:
![x=\frac{4\pm \sqrt{16-52}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%5Cpm%20%5Csqrt%7B16-52%7D%7D%7B2%7D)
Next, solve the subtraction:
![x=\frac{4\pm \sqrt{-36}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%5Cpm%20%5Csqrt%7B-36%7D%7D%7B2%7D)
Next, factor out i (i = √-1):
![x=\frac{4\pm \sqrt{36}i}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%5Cpm%20%5Csqrt%7B36%7Di%7D%7B2%7D)
Next, solve the square root:
![x=\frac{4\pm 6i}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%5Cpm%206i%7D%7B2%7D)
Lastly, divide and <u>your answer is:</u>
![x=2\pm 3i](https://tex.z-dn.net/?f=x%3D2%5Cpm%203i)
Yes, parallelogram congruent angles theorem
Answer:
The answer is B. f(x) = (x − 1)(x − 2)(x + 1)(x + 2)
Step-by-step explanation: